Characterization of Binary Biofilms of Listeria monocytogenes and Lactobacillus and Their Response to Chlorine Treatment - Olszewska, Magdalena A.; Diez-Gonzalez, Francisco (Frontiers in Microbiology, 2021)
In nature, Listeria may interact competitively and cooperatively with other organisms, resulting in unique spatial organization and functions for cells within the community. This study was undertaken to characterize the biofilm architecture of binary biofilms of L. monocytogenes and Lactobacillus species and to assess their effect on Listeria survival during exposure to hypochlorite. Three L. monocytogenes strains: ATCC 19115 (Lm5), ATCC 19117 (Lm7), and Coleslaw (LmC) were selected and combined individually with three Lactobacillus strains: L. fermentum (Lf), L. bavaricus (Lb), and L. plantarum (Lp). In binary Lm-Lp biofilms, the Lm cell counts were similar to single-species biofilms (8.5 log CFU/well) and the Lp cell numbers declined by 1.0 log CFU/well. In the presence of Lb, Lm cell counts were reduced by 1.5 log CFU/well (P<0.05), whereas the Lf cell count increased at least by 3.5 log CFU/well. Confocal laser scanning microscopy (CLSM) determined that interspecies interactions significantly affected the spatial organization of three binary biofilms. Biofilm surface to volume ratio increased from 0.8 µm2/µm3 for Lm5 in monoculture to 2.1 µm2/µm3 for Lm5–Lp in the dual-species model (P<0.05), and was characterized by a thicker structure with largely increased surface area. Biofilm roughness increased from 0.2 for Lm7 to 1.0 for Lm7–Lb biofilms (P<0.05), which appeared as interspecific segregation. Biofilm thickness increased from 34.2 µm for LmC to 46.3 µm for LmC–Lf (P<0.05), which produced flat and compact structures that covered the entire surface available. The biomass of the extracellular matrix was higher in the case of some binary biofilms (P<0.05), however, this effect was dependent upon the species pair. When treated with hypochlorite, Lm5 in binary biofilms had approx. 1.5 log CFU/well greater survival than individually. The unique spatial organization and greater protein production may explain the protective effect of Lp after hypochlorite exposure.